2018
DOI: 10.2147/ccid.s161352
|View full text |Cite
|
Sign up to set email alerts
|

Antiaging effects of a novel facial serum containing L-ascorbic acid, proteoglycans, and proteoglycan-stimulating tripeptide: ex vivo skin explant studies and in vivo clinical studies in women

Abstract: BackgroundWith age, decreasing dermal levels of proteoglycans, collagen, and elastin lead to the appearance of aged skin. Oxidation, largely driven by environmental factors, plays a central role.AimThe aim of this study was to assess the antiaging efficacy of a topical serum containing L-Ascorbic acid, soluble proteoglycans, low molecular weight hyaluronic acid, and a tripeptide in ex vivo and in vivo clinical studies.MethodsPhotoaging and photo-oxidative damage were induced in human skin explants by artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…30 Elastin is also an essential element of dermal connective tissue, imparting elastic and flexible properties to the skin. 31,32 Figure 5 shows the immunofluorescent labelling of procollagen type I and elastin in a hAec model.…”
Section: Ex Vivo Skin Modelsmentioning
confidence: 99%
“…30 Elastin is also an essential element of dermal connective tissue, imparting elastic and flexible properties to the skin. 31,32 Figure 5 shows the immunofluorescent labelling of procollagen type I and elastin in a hAec model.…”
Section: Ex Vivo Skin Modelsmentioning
confidence: 99%
“…Garre et.al, 2018 reported that topical serum containing L-Ascorbic acid, soluble proteoglycans, low molecular weight hyaluronic acid, and a tripeptideprotected against oxidative damage and dermal protein loss caused by photo-and chronological aging in human skin explants. In-vivo, the serum hydrated skin for 6 hours, and users perceived increased skin brightness, hydration, and fewer wrinkles [126]. Zasada et.al, 2019 reported that 2.5 ml of serum containing 20% L-ascorbic acid with hydrate from strawberries was used topically in every of 4 treatments.The impact of active substance on skin firmness and elasticity as well as the degree of hydration and skin tone was more efficient after micro-needle mesotherapy [127].…”
Section: Surface Roughnessmentioning
confidence: 99%
“…Vitamin C uptake from the plasma and transport across the skin layers is mediated by speci ic sodium-dependent vitamin C transporters (SVCTs) that are present throughout the Garre et al, 2018 reported that topical serum containing L-Ascorbic acid, soluble proteoglycans, low molecular weight hyaluronic acid, and a tripeptide protected against oxidative damage and dermal protein loss caused by photo-and chronological aging in human skin explants. In-vivo, the serum hydrated skin for 6 hours, and users perceived increased skin brightness, hydration, and fewer wrinkles [116]. Zasada et al, 2019 reported that 2.5 ml of serum containing 20% L-ascorbic acid with hydrate from strawberries was used topically in every of 4 treatments.…”
Section: Ascorbic Acid (Aa)mentioning
confidence: 99%